2012
DOI: 10.1186/1532-429x-14-45
|View full text |Cite
|
Sign up to set email alerts
|

Detection of thrombus size and protein content by ex vivo magnetization transfer and diffusion weighted MRI

Abstract: BackgroundTo utilize a rabbit model of plaque disruption to assess the accuracy of different magnetic resonance sequences [T1-weighted (T1W), T2-weighted (T2W), magnetization transfer (MT) and diffusion weighting (DW)] at 11.7 T for the ex vivo detection of size and composition of thrombus associated with disrupted plaques.MethodsAtherosclerosis was induced in the aorta of male New Zealand White rabbits (n = 17) by endothelial denudation and high-cholesterol diet. Subsequently, plaque disruption was induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
(24 reference statements)
2
12
0
Order By: Relevance
“…29 Similarly, ex vivo application of MT permitted the distinction between plateletrich and protein-rich thrombus in thrombosed rabbit plaque. 30 Here, we demonstrated the in vivo feasibility of MT for monitoring the evolution of venous thrombus at a clinically relevant field strength. MT uses saturation prepulses to destroy the magnetization of the bound-proton pool, resulting in images with reduced signal intensity that is proportional to the number of macromolecules.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…29 Similarly, ex vivo application of MT permitted the distinction between plateletrich and protein-rich thrombus in thrombosed rabbit plaque. 30 Here, we demonstrated the in vivo feasibility of MT for monitoring the evolution of venous thrombus at a clinically relevant field strength. MT uses saturation prepulses to destroy the magnetization of the bound-proton pool, resulting in images with reduced signal intensity that is proportional to the number of macromolecules.…”
Section: Discussionmentioning
confidence: 85%
“…41 The feasibility of using MT as an endogenous contrast mechanism to image the protein content of thrombus was demonstrated ex vivo using a catheter-based imaging MRI coil 28 and at high field. 30 Ex vivo measurement of the %MTR in human endarterectomy specimens showed that old (rich in protein debris) and recent (fibrin-rich) intraplaque hemorrhage had higher MTR compared with fresh intraplaque hemmorhage (rich in intact erythrocytes). 29 Similarly, ex vivo application of MT permitted the distinction between plateletrich and protein-rich thrombus in thrombosed rabbit plaque.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared with CUS, MRI can detect pelvic DVT and can more precisely define proximal (popliteal vein and above) and distal leg (below popliteal vein) DVT 8 , to better assess the risk of PE. MRI can characterize thrombus age and organization, and may help differentiate acute from chronic DVT [9][10][11] (refs updated). Quantification of thrombus volume, an important metric to assess the disease evolution and response to treatment, is feasible with MR imaging.…”
Section: Introductionmentioning
confidence: 99%